Optimizing The Role of Zakat Management Organizations in Managing The Impact of The Covid-19 Pandemic in Indonesia - Elif Pardiansyah; Muhammad Abduh; Muhammad Fakhrudin (PT. EQUATOR SINAR AKADEMIA, 2021)
The Zakat Management Organization (OPZ) is an organization that is authorized or appointed by the government to collect, manage and distribute public funds related to zakat. Apart from having an impact on public health, the Covid-19 pandemic also has an impact on cross-sectors such as the economy, education and social humanity. The three sectors that are affected and are of concern to the government today are micro, small and medium enterprises (MSMEs), vulnerable workers, and business actors in the tourism sector. In dealing with this situation, the zakat management organization (POZ) is expected to have an important role in helping the government in handling Covid-19, especially in handling the poor or mustahik who have just been affected by Covid-19.